Development of a camera-vision guided automatic sprayer - Wan Ismail, Wan Ishak; H., Hazlina; Awal, Md. Abdul (Universiti Putra Malaysia Press, 2008)
This study describes the design and development of a camera-vision guided unmanned mover sprayer for the purpose of automatic weed control. The sprayer system was mounted on the mover. Modifications were carried out for both sprayer and mover systems, so that it can be operated remotely. The automated system was developed using the electromechanical system and controllers. It is capable of directing the mover sprayer to the target location given by the user. The electromechanical system was developed to control the ignition, the accelerator and the spraying systems. The controllers consist of an I/O module (ICPCON I-87057) and also a pair of radio modems (SST-2400) for data transmission. The graphical user interface (GUI) software to control the automatic system was developed by using Visual Basic Programming. The GUI has features which enable the user to perform desired tasks using the computer instead of going directly to the sprayer/mover. The combination of the multi controllers and developed control software in the development of the camera-vision-guided unmanned mover sprayer can reduce drudgery and increase safety.